Lack of social support associated with major depressive disorder in middle-aged and older adults from the United States: A propensity score-matched cohort study - Ping Li; Kunlun Wu (PLoS ONE, 2026)
Background and objective Current widely used depression assessment criteria may not accurately reflect the true prevalence of depression, and previous studies have insufficiently addressed the multidimensional nature of social support . Research on the relationship between depression and specific dimensions of social support remains limited, which impedes the targeted allocation of scarce social resources to mitigate the disease burden. This study aimed to explore the association between multi-dimensional social support and major depressive disorder (MDD) in the US population, using depression assessment criteria consistent with current epidemiological data. Method We analyzed data from the National Health and Nutrition Examination Survey (NHANES). After propensity score matching (PSM), 123 participants with MDD (Patient Health Questionnaire-9 score ≥15) and 543 without MDD were included. Social support was assessed using five-dimensional questionnaires and each dimension was dichotomously scored (1 = presence of support, 0 = absence of support), yielding a total score ranging from 0 to 5. Participants were categorized into three social support groups: Low group (0–1), Middle group (2–3), and High group (4–5). Logistic regression models were used to examine the association between social support and MDD, and subgroup analyses were performed to assess consistency across populations. Results Compared with participants without MDD, those with MDD had significantly lower proportions of adequate social support across all five dimensions. Binary logistic regression analyses showed that higher social support levels were associated with a reduced risk of MDD (Middle vs Low group: odds ratio [OR], 0.40; 95% CI, 0.22–0.73; P = 0.003; High vs Low group: OR, 0.15; 95% CI, 0.08–0.29; P < 0.001). Financial support exhibited the strongest inverse association with MDD, while adequate religious activity showed the weakest inverse association. The relationship between social support and MDD remained consistent across all subgroup analyses. Conclusions In brief, sufficient social support, especially financial support, was linked to a significantly lower risk of MDD among the middle-aged and elderly population in the United States.